Communities of Practice and Linguistic Change: Perception of Gender-sensitive Language in Serbian Literary Translation (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper examines whether the standardization of gender-sensitive language is necessary for gender equality in language, and whether the use of gender-sensitive language automatically contributes to more equal male-female relations in the society. It also explores the possibility that the language is only a manifest of social reality, which is why efforts should be directed primarily to making Serbian society less discriminatory and its members more gender-sensitive. The concept of "communities of practice" provides a theoretical framework. The empirical part is a research conducted in a community of practice – the Association of Literary Translators of Serbia – in order to illustrate dominant views on gender-sensitive Serbian language in one part of the Serbian language elite. It is concluded that language activism is a necessary way to stop any elite from creating a discourse that promotes inequality in Serbian society. The linguistic activism will be effective and successful if implemented through everyday use of gender-sensitive language of interested communities of practice, which will lead to changes in discriminatory cultural patterns and ideologies.
Keywords: communities of practice; cultural models; gender equality; gender-sensitive language; language ideologies